A nonlinear analysis framework for bluff-body aerodynamics: A Volterra representation of the solution of Navier-Stokes equations. (April 2015) - Wu, Teng; Kareem, Ahsan
Abstract: A nonlinear analysis framework for bluff-body aerodynamics based on Volterra theory is introduced to capture the linear and nonlinear aerodynamic effects. The Volterra kernels based on the impulse function concept are identified by way of the simulation of Navier-Stokes equations using computational fluid dynamics (CFD). The computational schemes used here are validated through theoretical consideration, i.e., Blasius solution for the steady-state and Theodorsen solution for the system dynamic-state simulation. The source of nonlinearities in the aerodynamics of bluff bodies is systematically investigated. The simulation of bluff-body aerodynamics based on the Volterra reduced-order modeling scheme is obtained by the convolution of the identified kernels with the external inputs, e.g., turbulent inflow or body motion for aerodynamic or aeroelastic response, respectively. It is demonstrated that the Volterra theory-based nonlinear analysis framework for bluff-body aerodynamics combined with the identification of kernels using CFD promises to capture the salient features of bluff-body aerodynamics and offers an accurate reduced-order approximation of the Navier-Stokes equations with reduced level of computational effort.